Social mobility in Bolivia is finally improving! - Lykke E. Andersen (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2010)
This paper evaluates the degree of social mobility in Bolivia, both by comparing to other Latin American countries, and by comparing social mobility at different points in time. While Bolivia had one of the lowest levels of social mobility in the region in 1997, the last 10 years have seen spectacular improvements, especially for rural and female teenagers. This is very good news, as it suggests that Bolivia has finally escaped the low mobility - low growth equilibrium where it has been stuck for so long.
Keywords: E60; I32; J12; J13; 330; Social Mobility; Bolivia.